1975
DOI: 10.1007/bf02672164
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity and stability of 6‐hydroxy‐2,5,7,8‐tetramethylchroman‐2‐carboxylic acid

Abstract: Abstract6‐Hydroxy‐2,5,7,8‐tetramethylchroman‐2‐carboxylic acid in thin layer tests in vegetable oils and animal fats has two‐four times the antioxidant activity of butylated hydroxytoluene and butylated hydroxyanisole and is more active than propyl gallate, nordihydroquaiaretic acid, ascorbyl palmitate, and α‐ and γ‐tocopherols. It is also more active than tertiary butylhydroquinone in chicken and pork fats and corn, peanut, sunflower, and safflower oils in thin layer tests. Tertiary butylhydroquinone is sligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
2

Year Published

1981
1981
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(21 citation statements)
references
References 12 publications
2
17
0
2
Order By: Relevance
“…Yet, in active oxigen method, antioxidant index for TBHQ was 3-fold higher than for BHA and BHT. Higher antioxidative activity of TBHQ compared with BHA and BHT in model studies with soybean oil and chicken fat in emulsion versus dry oil tests was reported by Cort et al (6). Relative effectiveness of antioxidants-linoleic acid monolayer on silica gel for TBHQ was almost the same as for BHT, while for BHA almost 3-fold higher (9).…”
Section: Resultsmentioning
confidence: 57%
“…Yet, in active oxigen method, antioxidant index for TBHQ was 3-fold higher than for BHA and BHT. Higher antioxidative activity of TBHQ compared with BHA and BHT in model studies with soybean oil and chicken fat in emulsion versus dry oil tests was reported by Cort et al (6). Relative effectiveness of antioxidants-linoleic acid monolayer on silica gel for TBHQ was almost the same as for BHT, while for BHA almost 3-fold higher (9).…”
Section: Resultsmentioning
confidence: 57%
“…In contrast, 6-hydroxy-5,7, 8-trimethylchroman-2-carboxylic acid (Trolox C), an analog of a-tocopherol lacking the 2-trimethyldecyl side chain, was effective only at 20 pM, a 400-fold higher concentration. This compound does not show vitamin E activity (Kasparek, 1980) but is more potent than a-tocopherol in prevention of autoxidation of oils (Cort et al, 1975). Tocopherols are good antioxidants, however, and various antioxidants exhibit vitamin E activity in some systems (Schwarz, 1958a).…”
Section: Resultsmentioning
confidence: 98%
“…Although antioxidants substituted completely for a-tocopherol in the present cell culture system, the tocopherols were more potent than would be predicted from their activity in preventing autoxidation in chemical systems (Cort et al, 1975). Because tocopherols intercalate into cellular membranes (Packer, 1976), it is possible that they are more potent than simple antioxidants in certain biological systems by partitioning and exerting a selective antioxidant effect.…”
Section: *000mentioning
confidence: 93%
“…Esta substância apresenta propriedades antioxidante maiores que a das (Vitamina E) α e γ-tocoferol, tanto em gordura animal quanto vegetal (CORT et al, 1975). …”
Section: Trolox®unclassified